2019
DOI: 10.1007/s00209-019-02289-7
|View full text |Cite
|
Sign up to set email alerts
|

The Capelli eigenvalue problem for Lie superalgebras

Abstract: For a finite dimensional unital complex simple Jordan superalgebra J, the Tits-Kantor-Koecher construction yields a 3-graded Lie superalgebra g ♭ ∼ = g ♭ (−1) ⊕ g ♭ (0) ⊕ g ♭ (1), such that g ♭ (−1) ∼ = J. Set V := g ♭ (−1) * and g := g ♭ (0). In most cases, the space P(V ) of superpolynomials on V is a completely reducible and multiplicity-free representation of g, and there exists a direct sum decomposition P(V ) := λ∈Ω V λ , where (V λ ) λ∈Ω is a family of irreducible g-modules parametrized by a set of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…One can therefore deform this theory by two twisted masses u l , u r , so that the theory we discussed so far would correspond to the case u l + u r = 0. It is possible that such deformation also has an interesting Bethe/gauge dual (perhaps the generalized root systems of [55] would make an appearence, with κ/(1 − κ) = −u r /u l ). We propose another solidifier.…”
Section: A Family Of Theoriesmentioning
confidence: 99%
“…One can therefore deform this theory by two twisted masses u l , u r , so that the theory we discussed so far would correspond to the case u l + u r = 0. It is possible that such deformation also has an interesting Bethe/gauge dual (perhaps the generalized root systems of [55] would make an appearence, with κ/(1 − κ) = −u r /u l ). We propose another solidifier.…”
Section: A Family Of Theoriesmentioning
confidence: 99%
“…Now consider the osp(2|4)-module V = L(δ 1 + δ 2 − ǫ 1 ). We express S d (V * ) as a osp(2|4) × C-module with respect to the Borel b (−ǫ)δδ , following the presentation given in [SSS18]. There it was shown that S • (V * ) is completely reducible with the lattice of highest weights given by Λ…”
Section: Gl(1|2)mentioning
confidence: 99%
“…The representation theory of the space of functions as well as the algebra of invariant differential operators has been studied in recent years (see e.g. [SS16], [All12], [AS15], [SV17], [SSS18]). In [SSS18], the authors associate to each simple Jordan superalgebra J a supersymmetric pair (g, k) via the TKK construction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] to the common setting of multiplicity-free actions on Jordan superalgebras. This will be established in a forthcoming paper [24]. In addition, recently Sahi and Salmasian [23] constructed quadratic analogues of Capelli operators on Grassmannian manifolds by lifting the Capelli basis of [19] via a double fibration.…”
Section: Introductionmentioning
confidence: 96%